OPTIMALISASI APLIKASI MANAJEMEN KEUANGAN PRIBADI DENGAN SISTEM BUDGETING OTOMATIS BERBASIS MOBILE - Nugroho, Pramudiyanto; Asriningtias, Yuli (Jusikom : Jurnal Sistem Komputer Musirawas, 2025)
Users of personal finance applications frequently encounter difficulties in consistently documenting their daily transactions, the potential for inaccuracies in record-keeping, and a limited comprehension of budget distribution and spending behaviors. These challenges can result in financial disarray, excessive spending, and obstacles in saving planning. To mitigate these problems, an Android-based personal finance application has been developed, which incorporates both manual and automated transaction entry through Optical Character Recognition (OCR), automatic categorization of budgets into segments such as necessities, savings, and emergency funds, as well as intelligent alerts when budget limits are approached or when users have failed to log their daily transactions. Furthermore, the application offers engaging financial reports presented in graphical and tabular formats. Users also have the capability to export these reports in PDF format. Results from Blackbox testing demonstrate that all functionalities operate as intended, establishing this application as an efficient tool for assisting users in managing their finances in a more organized and responsive way.